The Concilium of Information Processing Networks of Chemical Oscillators for Determining Drug Response in Patients With Multiple Myeloma - Bose, Ashmita; Dittrich, Peter; Gorecki, Jerzy (Frontiers in Chemistry, 2022)
It can be expected that the medical treatment in the future will be individually tailored for each patient. Here we present a step towards personally addressed drug therapy. We consider multiple myeloma treatment with the drug named Bortezomib. It has been observed that this drug is effective for some patients and does not help others. We describe a network of chemical oscillators that can help to differentiate between non-responsive and responsive patients. In our numerical simulations, we consider a network of 3 interacting oscillators described with the Oregonator model. The input information is the gene expression value for one of 15 genes measured for patients with multiple myeloma. The single-gene networks optimized on a training set containing data of 239 therapies show up to 71% accuracy of differentiating between non-responsive and responsive patients. If the results of single-gene networks are combined into the concilium with the majority voting strategy, then the accuracy of predicting the patient’s response to Bortezomib therapy increases to ∼ 85 %.